Analysis of energy recovery and microbial community in an amalgamated CSTR-UASBs reactor for a three-stage anaerobic fermentation process of cornstalks - Bowei Zhao; Fei Xie; Aijuan Zhou; Zhihong Liu; Li Ji; Guixiang Zhang; Xiuping Yue (Water Science and Technology, 2022)
In this study, a continuous stirred-tank reactor (CSTR) coupled with up-flow anaerobic sludge beds (UASBs) reactor was successfully developed for enhancing methane production and carbon recovery rate from cornstalks. Acetic acid production was higher in regions A than in B and C. The methane percentage achieved at 75.98% of total gas and methane production of cornstalks was up to 520.07 mL/g, during the stable operation period. The carbon of recovery rate, represented substrates converted to methane gas, reached 69.32% in stable stage. Microbial community structure analysis revealed that Paludibacter, Prevotella/Clostridium sensu stricto, and Caldisericum were the dominant bacteria for the degradation of cellulose, lignin, and other refractory macromolecules in regions A, B, and C, respectively. Methanobacterium and Methanolinea were the two major genera, accounting for methanogenesis generation. HIGHLIGHTS Energy recovery, Three-stage fermentation, Cornstalks, CSTR-UASBs, Microbial community analysis.;